Prenatal onset of sporadic form of infantile cortical hyperostosis - Cohen, Lourdes (International Journal of Contemporary Pediatrics, 2018)
Infantile cortical hyperostosis, Caffey’s disease, is characterized by cortical swelling of one or several flat or long bones, fever, irritability and decreased movement of the affected bones. The onset of presentation is around ten weeks of age, however, antenatal cases with familial and sporadic forms have being reported. The etiology is unknown. Autosomal dominant or recessive inheritance and sporadic cases have been reported. Present case report describes a mild, antenatal and sporadic form of Caffey’s disease in a newborn infant, who presented with painless swelling and deformity of the right tibia and right forearm.